Pengembangan Media Pembelajaran E-komik IPA Pada Materi Sistem Pencernaan Manusia Untuk Siswa kelas VIII SMP: (Development of Science E-comic Learning Media on Human Digestive System Material for Class VIII Junior High School Students) - Putri Pancar Kasih; Muhaimin Muhaimin; Bambang Hariyadi (BIODIK, 2022)
Media is one of the important components that must exist in a learning process. The aim of this research is to develop science e-comic for human digestive system material for VIII-grade junior high school students. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data collection instrument used in the form of a validation questionnaire of design experts, material experts, teacher perceptions, and student perceptions of science e-comics. This research was conducted at SMP Insan Madani Boarding School Jambi. The results of validation by material experts obtained a percentage of 90.67% (very valid) and the assessment of media experts obtained a percentage of 90% (very valid). Assessment by the teacher obtained a percentage of 93.125% (very good). The results of the one-on-one trial obtained a total score of 96.67% (very good), the small-group trial scored 94.33% (very good), and the large group trial obtained a score of 92% (very good). In conclusion, science e-comic learning media is suitable for use in distance learning (online). Key words: Learning Media, E-Comic, Human Digestive System   Abstrak. Media merupakan salah satu komponen penting yang harus ada di dalam suatu pembelajaran. Tujan penelitian ini adalah mengembangkan e-komik IPA materi sistem pencernaan manusia untuk siswa kelas VIII SMP. Penelitian ini menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Instrumen pengumpulan data yang digunakan berupa angket validasi ahli desain, ahli materi,  persepsi guru dan persepsi siswa terhadap e-komik IPA. Penelitian ini dilakukan di SMP Insan Madani Boarding School Jambi. Hasil validasi oleh ahli materi memperoleh persentase 90,67% (sangat valid) dan penilaian ahli media memperoleh persentase 90% (sangat valid). Penilaian oleh  guru  memperoleh   persentase 93,125% (sangat baik). Hasil uji coba satu-satu diperoleh skor total 96,67% (sangat baik), uji coba kelompok kecil memperoleh nilai 94,33% (sangat baik), dan uji coba kelompok besar memperoleh nilai 92% (sangat baik). Kesimpulannya media pembelajaran e-komik IPA  layak digunakan dalam pembelajaran jarak jauh (daring). Kata kunci: Media Pembelajaran, E-komik, Sistem Pencernaan Manusia